Biochar from pulp and paper mill sludge : co-pyrolysis with bentonite, nutrient retention and leachability - Hetmanenko, Viktoriia; Krylach, Svitlana; Skrylnyk, Yevhen; Popirny, Maxim; Kutova, Angela (University of Bucharest, 2025)
Pulp and paper mills generate substantial sludge as a byproduct of wastewater treatment, offering a viable feedstock for biochar production. This study examines the potential of biochar derived from pulp and paper mill sludge to enhance nutrient management in manure handling and soil systems. Fiber sludges, classified as low-nutrient fiber and nutrientrich fiber, were pyrolyzed at 450°C, both individually and with a mineral additive. Co-pyrolysis with bentonite significantly increased the specific surface area and porosity of the biochar. Nutrient adsorption experiments using liquid pig slurry showed that the biochars retained 1.14-1.57% of total nitrogen and 0.54-0.78% of total phosphorus, with bentonite enhanced biochars demonstrating superior retention. Soil incubation and rainfall simulation experiments confirmed that nutrient-rich fiber biochars effectively reduced phosphorus leaching compared to conventional mineral fertilizers, whether produced alone or with bentonite. However, biochars from low-nutrient fiber led to nitrogen losses similar to mineral fertilizers. The Fourier infrared spectroscopy analysis revealed greater carbon stability in nutrient fiber biochars, highlighting the role of bentonite in enhancing biochar’s chemical stability.
Keywords: pyrolysis; sorption; nitrogen; phosphorus; percolation losses